Pengaruh Kolonial, Perlawanan, dan Identitas Budaya: Kajian tentang Bumi Manusia Karya Pramoedya Ananta Toer dan Kaitannya dengan Hukum Adat Buton - Cahyani, Nani; Malim, Dinna Dayana La Ode (Kainawa: Jurnal Pembangunan dan Budaya, 2024)
This study explores Pramoedya Ananta Toer’s This Earth of Mankind as a reflection of postcolonial cultural identity and resistance, comparing its insights to the Butonese people’s experience of identity preservation. The novel delves into tensions between traditional Javanese culture and Dutch colonial modernity, particularly through characters like Minke and Nyai Ontosoroh, who embody cultural hybridity and resistance, Postcolonial concepts, such as Homi Bhabha’s ‘Third Space’ are employed to analyze cultural shifts and empowerment offered through education. The Butonese people’s maritime culture and strategic location are examined as a case of sustaining identity amid external influences, showcasing parallels in navigating colonial legacies. The research question of this study is: how does This Earth of Mankind illustrate postcolonial influence, and how does its portrayal of cultural identity and resistance compare to the Butonese people’s efforts to preserve their culture? The study aims to explore postcolonial influence, cultural identity, and resistance in This Earth of Mankind and to analyze their relevance to the contemporary socio-cultural challenges of the Butonese people. The Methodology of this study, focusing on cultural identity shifts in Minke’s journey and its parallels with the postcolonial experiences of the Butonese people, supported by scholarly articles and webs to back up arguments. The theoretical framework of this study linking the narrative of This Earth of Mankind with Butonese people’s cultural identity and identity through applying theories of Homi Bhabha, Stuart Hall, and Geertz Clifford to explore hybrid and cultural identity. A key finding is that Dutch colonialism profoundly influenced the socio-political and economic systems of colonized communities like the Butonese. The Dutch introduced new administrative structures, economic policies, and social hierarchies that undermined traditional leadership and local economic practices. Despite these adversities, the Butonese showcased resilience by preserving their identity through their adat, spiritual traditions, and maritime practices. Another key insight is the role of hybridity in shaping identity and resistance among the Butonese. Drawing on Homi Bhabha’s theory, they blended Western influences like education and technology with their traditions, crafting new expressions of identity. Resistance emerged through both cultural affirmation and creative adaptation of customs, highlighting their resilience and adaptability against colonial authority.